(untitled) (Interdisciplinary Studies Journal, 2024)
For the development of the political-pedagogical projects of undergraduate courses in Veterinary Medicine in Brazil, some mandatory basic curriculum components must be included to ensure training inherent to professional practice. The present study aimed to analyze the curriculum frameworks of these courses, correlating the curriculum components and disciplines taught by field of study. Research and documentary analysis were conducted on curriculum frameworks of 196 courses. The curriculum frameworks have an average total workload of 4,547.6 hours. Of these, 3,815.7 hours consist of mandatory subjects, 459.8 hours of supervised curricular internship, 53.5 hours of the final course project, 96 hours of elective subjects, and 122.6 hours of complementary activities. Of the mandatory hours, 1,224.5 are allocated to Biological and Health Sciences, 299.1 to Humanities and Social Sciences, and 2,292.9 to Veterinary Medicine Sciences. It is concluded that Veterinary Medicine courses in Brazil have fulfilled the inclusion of mandatory components in their curricula. There are variations among states and regions in the distribution of workload. The North stood out with the highest workloads of mandatory and elective subjects, the Midwest for the final course project, and the South for the internship.